The changing economic advantage from private school - Francis Green; Stephen Machin; Richard Murphy; Yu Zhu (Institute for the Study of Labor (IZA), 2010)
Despite its relatively small size, the private school sector plays a prominent role in British society. This paper focuses on changing wage and education differentials between privately educated and state educated individuals in Britain. It reports evidence that the private/state school wage differential has risen significantly over time, despite the rising cost to sending children to private school. A significant factor underpinning this has been faster rising educational attainment for privately educated individuals. Despite these patterns of change, the proportion attending private school has not altered much, nor have the characteristics of those children (and their parents) attending private school. Taken together, our findings are consistent with the idea that the private school sector has been successful in transforming its ability to generate the academic outputs that are most in demand in the modern economy. Because of the increased earnings advantage, private school remains a good investment for parents who want to opt out, but it also contributes more to rising economic and social inequality.
Keywords: I22; I29; J31; 330; Returns to education; private schools; Karriereplanung; Einkommen; Bildungsabschluss; Privatschule; Großbritannien